2012
DOI: 10.1080/14786419.2011.570761
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and antimicrobial aporphine alkaloids fromFissistigma poilanei(Annonaceae) collected in Vietnam

Abstract: Two new aporphine alkaloids: 8-hydroxy-9-methoxy-1,2-methylenedioxyaporphine (1) and 8-hydroxy-3,9-dimethoxy-1,2-methylenedioxyaporphine (2) were isolated from the ethyl acetate extract of Fissistigma poilanei along with five known compounds: oxocrebanine (3), kuafumine (4), (2R,3R)-3',4',5,7-tetrahydroxydihydroflavonol-3-O-α-L-rhamnopyranoside (5), (+)-catechin 3-O-α-L-rhamnopyranoside (6) and quercetine 3,7-dimethoxy-3'-O-α-L-rhamnopyranosyl-(1 → 2)-β-D-glucopyranoside (7). These two new aporphine alkaloids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The syntheses of (+)-norglaucine (1) and (+)-nordicentrine (2) were completed by deprotection of the Boc groups in 12a/c respectively using anhydrous ZnBr2 (Scheme 3); the use of Brønsted acids (e.g. trifluoroacetic acid) led to low yields due to degradation of the sensitive aporphine products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The syntheses of (+)-norglaucine (1) and (+)-nordicentrine (2) were completed by deprotection of the Boc groups in 12a/c respectively using anhydrous ZnBr2 (Scheme 3); the use of Brønsted acids (e.g. trifluoroacetic acid) led to low yields due to degradation of the sensitive aporphine products.…”
Section: Resultsmentioning
confidence: 99%
“…The aporphines comprise a large group of plant-derived tetracyclic alkaloids featuring a 1,2,3,4-tetrahydroisoquinoline motif. Many members of the aporphine family display interesting biological activities, such as anti-inflammatory [1], antimicrobial [2], anticancer [3,4] and antiparasitic [5,6] properties. In the latter context, a handful of aporphines have been evaluated for bioactivity against protozoan parasites; for example dicentrine, isolated from Cassytha filiformis L., demonstrated antiparasitic activity against Trypanosoma T. brucei, potentially by acting as an intercalating agent with the parasite DNA (the kinetoplast) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The leaves of F. pallens have been used in traditional medicine for the treatment of abdominal pain, stomach pain, and diarrhea [1]. The chemical studies of Fissistigma genus indicated the presence of alcaloids, sesquiterpens, phenolics and flavonoids [2][3][4][5]. These compounds have shown the potential significant biological effects as cytotoxic and antimicrobial [5].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical studies of Fissistigma genus indicated the presence of alcaloids, sesquiterpens, phenolics and flavonoids [2][3][4][5]. These compounds have shown the potential significant biological effects as cytotoxic and antimicrobial [5]. However, a few phytochemical investigations of Fissistigma pallens have been studied [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Fissistigma (Annonaceae), comprises 100 species, is widely distributed in Africa, Asia, and Oceania. The phytochemical content of certain species of this genus were investigated such as F. maclurei [22], F. poilanei [23], F. latifolium [24], F. bracteolatum [25], F. cavaleriei [26], F. petelotii [27], F. oldhamii [28], F. acuminatissima [29], F. pallens [30], F. capitatum [29], F. rubiginosum [30], F. glaucescens [31], F. balansae [32], F. polyanthoides [33], F. polyanthum [34], F. kwangsiense [35], F. chloroneurum [29] and F. lanuginosum [36]. Alkaloids, flavonoids, triterpenoids, furanones, cyclopentenones, and benzenoids were reported from this genus [28,29,37,38].…”
mentioning
confidence: 99%